2017
DOI: 10.1038/nm.4297
|View full text |Cite|
|
Sign up to set email alerts
|

The cold-induced lipokine 12,13-diHOME promotes fatty acid transport into brown adipose tissue

Abstract: Brown adipose tissue (BAT) and beige adipose tissue combust fuels for heat production in adult humans, and so constitute an appealing target for the treatment of metabolic disorders such as obesity, diabetes and hyperlipidemia1,2. Cold exposure can enhance energy expenditure by activating BAT, and it has been shown to improve nutrient metabolism3–5. These therapies, however, are time consuming and uncomfortable, demonstrating the need for pharmacological interventions. Recently, lipids have been identified tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
338
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(364 citation statements)
references
References 38 publications
16
338
4
6
Order By: Relevance
“…We have previously identified 12,13-diHOME, an oxidized metabolite of linoleic acid, as a lipid biomarker of thermogenic activation (Lynes et al, 2017). In the present study, we focus on non-oxidized structural lipid species dynamics during thermogenic activation and identify phosphatidylglycerol and cardiolipin metabolism as one of the key metabolic pathways regulated in thermogenic fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously identified 12,13-diHOME, an oxidized metabolite of linoleic acid, as a lipid biomarker of thermogenic activation (Lynes et al, 2017). In the present study, we focus on non-oxidized structural lipid species dynamics during thermogenic activation and identify phosphatidylglycerol and cardiolipin metabolism as one of the key metabolic pathways regulated in thermogenic fat.…”
Section: Discussionmentioning
confidence: 99%
“…While these data are informative, a comprehensive database and tools for analyzing specific lipid species are still missing. In addition, although serum lipidomics from mice exposed to cold have recently been reported (Simcox et al, 2017), the circulating lipidome of humans exposed to cold exposure has been, thus far, limited to a small set of fewer than 100 oxidized lipid species (Lynes et al, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The diols formed from sEH action generally lack the activity of the epoxidized precursors however they are dramatically more polar, move rapidly out of cells, and are easily conjugated and excreted (Greene, et al, 2000). Yet, there is some evidence PUFA diols are chemoattractant for monocytes (Kundu, et al, 2013) and that linoleic diols specifically act as lipokines in the regulation of brown adipose tissue and thermogenesis (Lynes, et al, 2017). There is no overt phenotype with the whole body knockout animals not subjected to physiologic stress (Spector & Kim, 2015), however, knockout mice had lower survival following ischemic events (Hutchens, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…5B). The high levels and strong induction of Ephx2 mRNA in ground squirrel BAT resembles the cold-induction (1 h at 4°C) of Ephx2 in mice leading to 12,13-diHOME production and the resulting increase in BAT fatty acid transport (Lynes et al, 2017). In natural hibernators, seasonal induction of Ephx2 suggests that ground squirrels and possibly other hibernating mammals have the potential to provide additional biochemical clues for increasing BAT size and function.…”
Section: Lipokine Regulation Of Batmentioning
confidence: 89%
“…Despite the overall improvement in fat catabolism and the potential for weight loss, cold exposure is uncomfortable and not well-tolerated by nonhibernators. In March 2017, Tseng and colleagues (Lynes et al, 2017) showed that the lipid 12,13-dihydroxy-9Z-octadecenoic acid (12,13-diHOME) stimulates BAT activity in mice. Injection of 12,13-diHOME activates the uptake of fuel into mouse BAT, resulting in lowered levels of serum triglycerides and improved tolerance of cold temperatures.…”
Section: Lipokine Regulation Of Batmentioning
confidence: 99%